Effects of fundamental movement skills on health-related quality of life in Chinese school-age children: the mediating role of physical fitness level - Shuqing Xie; Yulan Zhou; Yanmin Yin; Rui Shao; Lei Fang; Weide Shao (Frontiers Media S.A., 2023)
BackgroundThe primary purpose of this study is to analyze the relationship between school-age children's fundamental movement skills (FMS), physical fitness levels, and the health-related quality of life (HRQoL); To explore the mediating role of physical fitness levels between school-age children's FMS and HRQoL.MethodsIn the cross-sectional survey in 2021, 334 school-age children aged 6-10 (8.20 ± 1.16) were recruited from primary schools in Jinhua City, Zhejiang Province, China. Test of Gross Motor Development 2 (TGMD-2), National Standards for Students' Physical Health, and Pediatric Quality of Life Inventory TM Version 4.0 (PedsQL™ 4.0) were used to investigate the FMS, physical fitness level, and HRQoL of school-age children. Hierarchical regression was used to analyze the relationship among FMS, physical fitness levels, and HRQoL. Bootstrap is used to evaluate the mediating role of physical fitness levels in the relationship between FMS and HRQoL.ResultsThe higher the FMS and physical fitness, the higher the school-age children's HRQoL, physical functioning, social functioning, and school functioning (r = 0.244-0.301, p < 0.01). In addition, developing children's FMS promotes physical fitness levels (r = 0.358, p < 0.01). The regression analysis results of controlling gender, age, and body mass index z (BMI-z) scores showed that FMS significantly positively predicted the physical functioning (β = 0.319, p < 0.01), social functioning (β = 0.425, p < 0.01), and school functioning (β = 0.333, p < 0.01) of school-age children. When the physical fitness level enters the regression equation, the absolute value of the regression coefficient of FMS decreases. However, it can still significantly predict the physical functioning (β = 0.211, p < 0.01) and school functioning (β = 0.142, p < 0.05) of school-age children. Simple intermediary analysis shows that physical fitness level plays an intermediary role between FMS, physical functioning (indirect effect = 0.089 [95% Confidence interval (CI) = 0.015,0.195]), and school functioning (indirect effect = 0.065 [95% CI = 0.007,0.150]).ConclusionThis study shows that physical fitness levels mediate the relationship between FMS and HRQoL. Encouraging the development of FMS and promoting physical fitness levels of school-age children can effectively improve the HRQoL of school-age children.